1992
DOI: 10.1111/j.1365-2796.1992.tb00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year survivors with multiple myeloma

Abstract: Of 130 Japanese patients with symptomatic multiple myeloma who were treated between 1970 and 1989, nine (6.9%) patients survived for more than 10 years. Younger age, low and intermediate tumour mass, chemotherapy with cyclophosphamide, the disappearance of myeloma protein, and a positive response to retreatment were correlated with long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This indicates that the extensive skeletal involvement should not be strictly considered a poor prognostic factor. Conversely, in the same studies [11][12][13][14][15][16] the absence of renal failure at presentation in patients with prolonged survival showed that this feature is a favourable prognostic factor. Three of our patients presented with renal impairment at diagnosis.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This indicates that the extensive skeletal involvement should not be strictly considered a poor prognostic factor. Conversely, in the same studies [11][12][13][14][15][16] the absence of renal failure at presentation in patients with prolonged survival showed that this feature is a favourable prognostic factor. Three of our patients presented with renal impairment at diagnosis.…”
Section: Discussionmentioning
confidence: 85%
“…In similar reports [11][12][13][14][15][16] dealing with MM patients surviving ≥10 years, aged ≤65 years, with a low and intermediate tumour mass, response to initial chemotherapy and good control of relapsing disease were regarded as favourable factors. It is noteworthy that in almost all longsurviving patients, including 17 of our 21, extensive lytic bone lesions were observed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation